The Solution of Applied Problems of Complex Compounds with the d-Elements Central Atoms Surrounded by Octahedral Ligand Based on the Theory of Crystal Field - Tatarchuk, T. R.; Sirenko, H. O.; Kush, U. L. (Physics and Chemistry of Solid State, 2015)
The crystal field theory as applied to complex compounds of d-elements surrounded by octahedral ligans was described. Ligand field causes the splitting of d-orbitals, which is characterized by the energy splitting Δo. The spectrochemical series of ligands and examples of high-spin and low-spin complex compounds depending on the degree of force field were presented. Deformation of octahedral complexes by the Jahn-Teller effect was described. It shows the calculation of gains power as a result of complex formation, called the crystal field stabilization energy (CFSE) depending on the electronic structure of the central ion and the ligand position in spectrochemical series. It shows the distribution of electrons in orbitals of eg and t2g complex ions with different electronic configurations (from d1 to d10), examples values of energy orbitals and energy of crystal field stabilization for high-spin and low-spin octahedral complexes.